Superconductivity in Metal-Rich Chalcogenide Ta(2)Se - Gui, Xin (Inorg Chem, 2020)
[Image: see text] The metal–metal bond in metal-rich chalcogenide is known to exhibit various structures and interesting physical properties. Ta(2)Se can be obtained by both arc-melting and solid-state pellet methods. Ta(2)Se crystallizes a layered tetragonal structure with space group P4/nmm (No. 129; Pearson symbol tP6). Each unit cell consists of four layers of body-centered close-packing Ta atoms sandwiched between two square nets of Se atoms, forming the Se–Ta–Ta–Ta–Ta–Se networks. Herein, we present magnetic susceptibility, resistivity, and heat capacity measurements on Ta(2)Se, which together indicate bulk superconductivity with T(c) = 3.8(1) K. According to first-principles calculations, the d orbitals in Ta atoms dominate the Fermi level in Ta(2)Se. The flat bands at the Γ point in the Brillouin zone yield the van Hove singularities in the density of states around the Fermi level, which is intensified by introducing a spin–orbit coupling effect, and thus could be critical for the superconductivity in Ta(2)Se. The physical properties, especially superconductivity, are completely different from those of Ta-rich alloys or transition-metal dichalcogenide TaSe(2).